MARKETING STRATEGIES OF ENTERPRISES IN THE FOOD MARKET AS A KEY FACTOR OF THEIR COMPETITIVENESS (Development Service Industry Management, 2024)
The purpose of this article is to analyze modern marketing strategies that allow food industry enterprises to achieve sustainable competitive success.One of the main issues is the high competition in the food market, constant changes in consumer preferences and increasing requirements for product quality and safety. The modern food market is a highly competitive environment, where consumer preferences are constantly changing and requirements for product quality and safety are increasing. In such conditions, the effectiveness of marketing strategies is a determining factor in the success of enterprises.This work is devoted to a comprehensive analysis of marketing strategies in the food market. The purpose of the study is to systematize theoretical foundations and empirical data on marketing strategies, identify their impact on the competitiveness of enterprises and develop recommendations for increasing the effectiveness of marketing activities.To achieve this goal, a detailed analysis of current trends in the food market was conducted, key consumer segments and their needs were identified, the competitive environment was assessed and differentiation strategies were developed. In addition, the role of digital technologies in food marketing was assessed and a model of an effective marketing strategy for food industry enterprises was developed.The study expands theoretical ideas about marketing strategies in the food market, offers new approaches to consumer segmentation and the development of marketing programs. The results of the study can be used by managers of food industry enterprises to develop effective marketing strategies, increase competitiveness and increase sales. In addition, the data obtained can be useful for developing state policy in the food industry.
Keywords: food marketing; competitiveness; market segmentation